Undergraduate pharmacy students' motivations, satisfaction levels, and future career plans. Issue 3 (June 2018) - Alhaddad, Mahmoud S.
الملخص: أهداف البحث: هدفت هذه الدراسة إلى تقييم أسباب الانضمام إلى برنامج الصيدلة بين طلاب البكالوريوس في الصيدلة، ورضاهم عن الاختيار والخطط الوظيفية المستقبلية. طرق البحث: تم تبني تصميما بحثيا مستعرضا باستخدام أسلوب أخذ العينات بطريقة سهلة وغير احتمالية. وتمت دعوة جميع طلاب البكالوريوس في الصيدلة في إحدى الجامعات الحكومية في المملكة العربية السعودية للمشاركة في هذه الدراسة. النتائج: أجاب ما مجموعه ٣٩٨ مشاركا على الاستبانة. وكانت الأسباب الرئيسة لدراسة برنامج الصيدلة هي تأثير الأسرة (٦٦.٦٪)، والبحث عن وظيفة ذات فرص متنوعة (٨١.٧٪) والتطلع إلى العمل في مهنة تتعلق بالصحة (٨٣.٤٪). بالإضافة إلى ذلك، ذكر ٥٨٪ من المستجيبين أنه لو تم منحهم فرصة اختيار برنامجهم الجامعي، فإنهم سيختارون برنامج الصيدلة. العمل كصيادلة سريريين في المستشفى كانت الخطة الوظيفية الرئيسة المستقبلية كما اقترح ٨٣.٢٪ من المستجيبين. الاستنتاجات: هناك حاجة لتوجيه طلاب المدارس الثانوية في اختيار برامجهم الجامعية. وهناك حاجة لإفهامهم التحديات والفرص المصاحبة لدراسة الصيدلة. يمكن تحقيق ذلك بتنظيم برنامج تعريفي صيدلي لمدة يوم واحد يقدم للطلاب خلال مرحلة تعليمهم الثانوي. Abstract: Objectives: This study aims to evaluate undergraduate pharmacy students' reasons for joining the pharmacy program, their levels of satisfaction regarding their choice, and their future career plans. Methods: A cross-sectional research design was adopted using a non-probability convenience sampling technique. All undergraduate pharmacy students at one public university in KSA were invited to participate in the study. Results: A total of 398 participants responded to the questionnaire. Family influence (66.6%), seeking a job with diverse opportunities (81.7%), and the desire to work in a health-related profession (83.4%) were the main reasons for studying pharmacy. Only 58% of respondents affirmed that, given the chance to choose their undergraduate program again, they would still choose pharmacy. Working as a hospital clinical pharmacist was the most popular future career plan, cited by 83.2% of respondents. Conclusion: There is a need to guide high school students regarding their choice of undergraduate programs, and for these students to be made aware of the challenges and opportunities of studying pharmacy. This can be achieved by organizing a one-day pharmacy orientation program introduced to students during their high school education.